Proceedings 2019 Network and Distributed System Security Symposium 2019
DOI: 10.14722/ndss.2019.23392
|View full text |Cite
|
Sign up to set email alerts
|

Quantity vs. Quality: Evaluating User Interest Profiles Using Ad Preference Managers

Abstract: Widely reported privacy issues concerning major online advertising platforms (e.g., Facebook) have heightened concerns among users about the data that is collected about them. However, while we have a comprehensive understanding who collects data on users, as well as how tracking is implemented, there is still a significant gap in our understanding: what information do advertisers actually infer about users, and is this information accurate? In this study, we leverage Ad Preference Managers (APMs) as a lens th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…This outcome also aligns with real-world tracking. Prior work has documented the poor accuracy of behavioral profiles built by online advertisers [74,89], with one study finding only 27% of inferences were strongly relevant [9]. At least 40% of attributes sold by data brokers may be inaccurate [93].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This outcome also aligns with real-world tracking. Prior work has documented the poor accuracy of behavioral profiles built by online advertisers [74,89], with one study finding only 27% of inferences were strongly relevant [9]. At least 40% of attributes sold by data brokers may be inaccurate [93].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Google's Ad Settings (Figure 1b) lists some estimated interests and gives vague explanations of how they were chosen. These dashboards have been shown to be incomplete [89,99], misleading [4], and potentially inaccurate [9,21]. They have also been used to show discrimination in advertising [20] and targeting on sensitive topics [48,99].…”
Section: Privacy Tools and Transparencymentioning
confidence: 99%
“…and 507 respectively). While the non-sensitive categories may not directly reveal private information about the user, they are typically part of Ad Preference Manager profiles [17] and can be leveraged by advertisers for user targeting [30]. Moreover, websites that are susceptible to fine-grained history sniffing (see Section VI-C) could enable the inference of sensitive data.…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…Finally, a number of recent studies have examined the accuracy of information revealed by the transparency mechanisms of online advertising platforms. While one study [50] found that participants' age and gender as revealed by Google's transparency mechanism were accurate for 65% -74% of participants, and had missing values for 18%-29% of participants; another study [14] found that over 52% of participants reported less than half of their information as listed by the transparency mechanisms of Google, Facebook, and a small broker Nielsen eXelate as "relevant". Finally, 27% of users in a recent report [1] found their information revealed by Facebook's transparency mechanism inaccurate.…”
Section: Related Workmentioning
confidence: 99%